Optimization of Linear Quadratic Regulator (LQR) and Linear Quadratic Tracking (LQT) Systems - Muhammad Izzul Haj; Anggara Trisna Nugraha (Journal of Marine Electrical and Electronic Technology, 2025)
The increasing demand for high performance systems has triggered the emergence of optimal control problems which have become a hot topic recently. Related to the concept of how the condition of an optimal control system is the concept of optimizing a control system which shows a balance in the form of a meeting point between selecting a performance index and engineering with the aim of creating an optimal control system within the limits of physical constraints. In creating these conditions, it is necessary to have control system decision rules that can reduce the savings value from ideal behavior. In compiling this report, the author will explain the application of the LQR and LQT DC Motor Plant processes which are equipped with a datasheet. The use of MATLAB is also needed in the preparation of this report to include datasheets in the MATLAB script which will then be simulated with MATLAB Simulink. The purpose of this process is to see how the step response is generated. Meanwhile, the type of DC motor used is type C24-L50, equipped with values for moment of inertia, damping ratio, inductance, resistance, and motor constants. in carrying out the experiment there is no series that is designed to reach the desired set point of the scope graph, because the application of a mathematical model from an existing data sheet does not use damping so that the graph cannot reach the set point.